Strategi Komunikasi dalam Tradisi Pembuatan Gerabah Banyuning - I Kadek Edi Palguna; I Nyoman Buda Asmara Putra; Kadek Abdhi Yasa (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Banyuning pottery seems to have decreased in quantity in the modern era, due to very high competition with similar products made with modern technology. If there is no good inheritance system in the pottery-making tradition, it is likely that the tools in the form of pottery will be shifted by tools produced in a modern way, and lead to the extinction of the tradition. In this case, there needs to be a good communication so that the inherited tradition can continue. The purpose of this study was to find out the communication strategy carried out by craftsmen in the sustainability of the pottery-making tradition in Banyuning Village and what the implications of this strategy were. In this study using qualitative methods, data collection was done through observation, literature study and conducting interviews. Primary and secondary data were then analyzed and presented descriptively. The theory used in dissecting the research problem is the theory of social learning and the theory of diffusion of innovation. The results of the study show that the craftsmen have inherited persuasive communication to the younger generation in order to grow a sense of belonging and want to continue the tradition of making pottery. Craftsmen also began to innovate and make creative pottery crafts following current trends. The implications of communication strategies in the inheritance of the Banyuning pottery-making tradition are being able to raise awareness of one's own culture, the emergence of a sense of belonging to cultural products, the growing interest in pottery making, so that the pottery-making tradition in Banyuning Village can survive.